THEORETICAL PERSPECTIVES ON CONDITIONAL RELATIONSHIPS IN LINGUISTICS: A COGNITIVE AND FUNCTIONAL APPROACH - Tursuntosh Isroilova (Modern American Journals, 2025)
Conditional relationships represent one of the most fundamental logical and linguistic mechanisms that connect propositions and reflect the structure of human reasoning. Over the centuries, scholars have explored how humans conceptualize and linguistically encode dependence between events, actions, and outcomes. This article investigates the theoretical and functional foundations of conditional relationships in linguistics, drawing from traditional logic, semantics, pragmatics, and cognitive linguistics. The research discusses the historical background of conditionals from Aristotle’s syllogistic logic to contemporary cognitive approaches proposed by scholars such as Sweetser (1990) and Fauconnier (1994). Moreover, the study addresses cross-linguistic variation in expressing conditionality, focusing on structural and semantic differences between English and Turkic languages, particularly Uzbek. Through a synthesis of functional-semantic field theory and cognitive frameworks, the paper highlights the integral role of conditional constructions in linking grammar, logic, and cognition. The study concludes that conditional relationships serve as a linguistic embodiment of human hypothetical reasoning and cognitive mapping of causality and possibility.
Keywords: Cultural competence, Uzbek folk dance, Folklore motifs, Pedagogical methodology, Student development